Physician Characteristics Associated With Sugar-Sweetened Beverage Counseling Practices. Issue 6 (July 2018) - VanFrank, Brenna K.; Park, Sohyun; Foltz, Jennifer L.; McGuire, Lisa C.; Harris, Diane M.
Purpose: Frequent sugar-sweetened beverage (SSB) consumption is associated with chronic disease. Although physician counseling can positively affect patient behavior, physicians' personal characteristics may influence counseling practices. We explored SSB-related topics physicians discuss when counseling overweight/obese patients and examined associations between physicians' SSB-related counseling practices and their personal and medical practice characteristics. Design: Cross-sectional survey. Setting: DocStyles survey, 2014. Participants: A total of 1510 practicing US physicians. Measures: Physician's SSB counseling on calories, added sugars, obesity/weight gain, health effects, consumption frequency, water substitution, and referral. Analysis: Adjusted odds ratios (aORs) were calculated with multivariable logistic regression, adjusting for physician's personal and medical practice characteristics. Results: Most physicians (98.5%) reported SSB-related counseling. The most reported topic was obesity/weight gain (81.4%); the least reported were added sugars (53.1%) and referral (35.0%). Physicians in adult-focused specialties had lower odds than pediatricians of counseling on several topics (aOR range: 0.26-0.64). Outpatient physicians had higher odds than inpatient physicians of counseling on consumption frequency and water substitution (aOR range: 1.60-2.01). Physicians consuming SSBs ≥1 time/day (15.7%) had lower odds than nonconsumers of counseling on most topics (aOR range: 0.58-0.68). Conclusion: Most physicians reported SSB-related counseling; obesity/weight gain was discussed most frequently. Counseling opportunities remain in other topic areas. Opportunities also exist to strengthen SSB counseling practices in adult-focused specialties, inpatient settings, and among physicians who consume SSBs daily.